Effect of elevated temperature and CO2 on growth of two early-maturing potato (Solanum tuberosum L.) varieties - Liu, C.; Li, Y.; Liu, Y.; Kear, P.; Feng, Y.; Wang, L.; Wang, D.; Luo, M.; Li, J. (Elsevier, 2025)
Climate change will significantly reduce potato yields across the world and have a profound impact on food security. However, the effects of changing climatic conditions on various traits of early-maturing potatoes at their different stages of growth are not clear. Therefore, 19 plant traits were investigated across the entire growth period of two major early-maturing potato varieties: Favorita and Zhongshu 5. These were grown in a temperature/CO2-controlled walk-in chamber under four treatments that simulated the changes predicted in these two climate factors by 2100: Control (ambient temperature 21 °C; ambient CO2 400 μmol mol-1), eT (elevated temperature 24 °C; ambient CO2 400 μmol mol-1), eCO2 (ambient temperature, 21 °C; elevated CO2 800 μmol mol-1), and eTeCO2 (elevated temperature 24 °C; elevated CO2 800 μmol mol-1). Elevating ambient temperature by 3 °C (eT), elevating CO2 concentration to 800 μmol mol-1 (eCO2), and a combination of both treatments (eTeCO2) brought forward potato tuber initiation by approximately 10 days. eT treatment reduced the yield of Favorita by 83% and Zhongshu 5 by 52%, but simultaneously elevating the CO2 concentration (eTeCO2) alleviated the negative effects of higher temperature on plant morphology and biomass. Favorita exhibited greater stability than Zhongshu 5 under all treatment conditions. These findings will guide the development, cultivation, and research of climate-resilient potatoes as an adaptation to climate change to strengthen food security.